Sustainable Management Model Of Pasir Pengaraian Urban Forest - Arifin, Muzayyinul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Urban forests have a vital role in supporting the sustainability of urban development. This study aims to formulate a sustainable management model for Pasir Pengaraian Urban Forest using a mixed method approach. This study includes institutional analysis, identification of appropriate plant species, and development zoning mapping. A qualitative approach is used to examine institutional management and stakeholder participation, while a quantitative approach is used to evaluate ecological, social, and economic factors. The results of the study indicate that the management of Pasir Pengaraian Urban Forest requires integrated planning and development as well as strengthening of community participation-based management policies. In addition, optimization of the ecological, social, and economic functions of urban forests can be achieved through vegetation maintenance, management zoning, and periodic monitoring. This management model is expected to contribute to creating a better balance of urban ecosystems and strengthening the sustainability of regional development in Rokan Hulu Regency